56=2x+2(2x-5)

Simple and best practice solution for 56=2x+2(2x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 56=2x+2(2x-5) equation:


Simplifying
56 = 2x + 2(2x + -5)

Reorder the terms:
56 = 2x + 2(-5 + 2x)
56 = 2x + (-5 * 2 + 2x * 2)
56 = 2x + (-10 + 4x)

Reorder the terms:
56 = -10 + 2x + 4x

Combine like terms: 2x + 4x = 6x
56 = -10 + 6x

Solving
56 = -10 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
56 + -6x = -10 + 6x + -6x

Combine like terms: 6x + -6x = 0
56 + -6x = -10 + 0
56 + -6x = -10

Add '-56' to each side of the equation.
56 + -56 + -6x = -10 + -56

Combine like terms: 56 + -56 = 0
0 + -6x = -10 + -56
-6x = -10 + -56

Combine like terms: -10 + -56 = -66
-6x = -66

Divide each side by '-6'.
x = 11

Simplifying
x = 11

See similar equations:

| 1x+20=50-6 | | 7-wx=vx+4 | | 9+s=21 | | 2*74+2*130= | | .25(x+8)=2x-.5 | | 19-7z=3-5z+3 | | -3x+2=8x+-1 | | 6x-5w+5x+7y+4y+3w= | | -3x+2=8x-1 | | 9+4q=1 | | 6x-6x-9x=99 | | 3*4*-2=x | | 3x^3+3x-6x=0 | | -6x-12=10+5x | | s(t)=-t^3+13t^2-40t | | 3c+4=11c | | -18=3(-a+6)+2z | | (7x^2-8)+(3x^2+1)= | | 13-4z=2z+9 | | 2x+2=-3x+6 | | 2x+2=4x+-6 | | cos(7x+ln(5x))=0 | | lx^2+3x+1l=1 | | 9-3x+2=10-3x | | 20+0.07(x-20)=0.06x | | 3u^2+3v^2-6uv+20u-20v+12=0 | | 1x-3y=14 | | Xy-4x+10=0 | | 9x+11=5x+1 | | 20+0.07x=0.06x | | x+9+2x=30 | | 11+2a=14 |

Equations solver categories